Genetic variation and evolutionary analysis of broad bean wilt virus 2 - Ferrer, Rosa M.; Ferriol, Inmaculada; Moreno, Pedro; Guerri, José; Rubio, Luis (2017)
The genetic variation and evolutionary mechanisms of broad bean wilt virus 2 (BBWV-2) were studied by nucleotide sequence analysis of four genomic regions of 30 isolates from different countries. Nucleotide diversity was high (0.198) for a plant virus. Phylogenetic and genetic structure analyses showed low population subdivision, suggesting a significant gene flow between distant geographic areas. Analysis of synonymous and nonsynonymous substitutions showed different negative selection pressures for different parts of the coding regions, but no positive selection was found. Several recombination detection methods showed that some BBWV-2 genomes might have originated from recombination or reassortment.